Work Postural Analysis and Individual Characteristics with Musculoskeletal Disorder's Occurrance in Formal Sector Employees at PT Bumi Suksesindo Pesanggaran Banyuwangi - Luluk Faridatul Mukaromah; Al Munawir; Hadi Prayitno (Health Notions, 2019)
Musculoskeletal Disorders is a group of symptoms that affect the normal functions of the smooth tissue of the musculoskeletal system which accumulates continuously over a relatively long time which can be in a matter of days, months and years, depending on the severity of the trauma. Preliminary studies conducted by researchers at PT. Bumi Suksesindo Banyuwangi revealed that the prevalence using the Nordic Body Map questionnaire on 15 workers found that there were MSDs complaints both at work and at the time they finished working. PT.Bumi Suksesindo is one of the gold mining companies in Banyuwangi which 90% of the administrative staff at PT. Bumi Suksesindo works by using a computer with a sitting position and has individual characteristics in the form of gender, age, BMI, years of service, smoking habits and exercise habits. The purpose of this study was to analyze the relationship between work posture and individual characteristics (gender, age, years of service, smoking habits, and exercise habits) with the incidence of musculoskeletal disorders (MSDs) in formal sector employees of PT. Bumi Suksesindo Pesanggaran Banyuwangi. This research was quantitative with analytic observational method with Cross Sectional design. The sample of this study was 45 formal sector employees at PT. Bumi Suksesindo Banyuwangi which were taken by using simple random sampling. Logistics regression was used to analyze the data. Based on the test results, there was a relationship of age (p-value: 0,000), BMI (p-value: 0,023) smoking habits (p-value: 0,003) and exercise habits (p-value: 0,000) on MSDS existence. Keywords: work postural; individual characteristic; musculoskeletal disorder’s